Effects of in vitro gastrointestinal digestion on phenolic compounds and antioxidant activity of different white winemaking byproducts extracts. (July 2018) - José Jara-Palacios, M.; Gonçalves, Sandra; Hernanz, Dolores; Heredia, Francisco J.; Romano, Anabela
Abstract: The effect of in vitro gastrointestinal digestion on phenolic composition and antioxidant activity of different white winemaking byproducts extracts (grape pomace and its parts: seeds, skins and stems) was evaluated. Fourteen individual phenolic compounds were evaluated by UHPLC. The antioxidant activity was measured by DPPH and ORAC assays. Differences on phenolic profile and antioxidant activity were observed depending on the digestion phase, the type of byproduct, the phenolic group and the antioxidant activity assay. In general, digestion had a reducing effect on TPC and antioxidant activity; however, ORAC values of seed and stem extracts increased after digestion and some recovery indexes of the phenolic groups were very high. Results indicate that extracts from white winemaking byproducts are a reliable source of bioaccessible antioxidant compounds, which could be used as functional food ingredients. Graphical abstract: Highlights: White winemaking byproducts (seed, skin, stem and pomace) were subjected to in vitro digestion. Digestion greatly affected the phenolic composition and antioxidant activity. Effects of digestion were different according to the type of byproduct. Total phenolics decreased although some individual phenolics showed high stability. These byproducts are a reliable source of bioaccessible antioxidant compounds.